SOCIETY-NATURE RELATIONSHIP AND ENVIRONMENTAL DEGRADATION IN CAPITALIST PRODUCTION: A SYNTHESIS EFFORT - Santana, Alessandro Donaire de [UNESP]; Rodrigues Nunes, Joao Osvaldo [UNESP] (Univ Federal Goias, Dept Geografia, 2021)
Geography takes precedence in the analysis and understanding of the phenomena materialised in the geographic space considering the multiple nuances of the society-nature relationship and its underlying contradictions. Therefore, this article presents the main elements constituting the modus operandi of the abovementioned relationship. This is realised by considering capitalism and its development model anchored in the massive exploitation of natural resources, the role of the state in regulating the performance of agents of economic power in the production of space and subsequently, the environmental degradation resulting from that process. This analysis also shows the deepening inequality in the relationship between the central nations, the biggest consumers of natural resources and the peripheral ones, which are still eminent suppliers of primary products. The peripheral nations are also the ones that suffer the most from the environmental impacts in their territories. In this context, Brazil emerges as one of the greatest exponents of this harmful logic. Therefore, it is necessary to change the patterns that will allow the birth of new forms of the relationship between humanity and nature, thereby reducing the serious environmental degradation that has been observed in recent times.
Keywords: Nature; Capitalism; Environmental impacts